سيميائية الذوات الدرامية في نص مسرحية "الوردة والسياف" لـ عز الدين ميهوبي - بن ستيتى، سعدية (اتحاد الجامعات العربية - الجمعية العلمية لكليات الآداب, 2020)
يقوم البرنامج الدرامي في النص المسرحي على مجموعة من التحولات الدرامية وفق إطار زمني ومكاني محددين، يحاول الكاتب تجسيده عبر فضاء متخيل مرافقة بنص مواز يشرح فيه وضعيات وقوع الأفعال الدرامية، ويصف فيه أيضا حالات الذوات الفاعلة القائمة على تحريك الفعل الدرامي وتحويله من مسار إلى آخر في عملية تسمى في المصطلح السيميائي بالتحولات الدرامية. على هذا الأساس فالذات الدرامية هي بؤرة النص المسرحي، ويقوم الفعل الدرامي أصلا بوجودها عن طريق تحديد علاقتها بموضوع القيمة الذي يجسده النص المسرحي، سواء أكانت الذات الفاعلة متصلة بالموضوع أم منفصلة عنه، فالذات الفاعلة تبرز هيمنة على المسار الدرامي في النص المسرحي سواء أكانت سلبية أم إيجابية. وبناء على ذلك، اتجهت دراستنا في هذا العمل إلى متابعة ذوات الفعل الدرامي في مسرحية "الوردة والسياف" للكاتب المسرحي والشاعر "عز الدين ميهوبي" وفق المنهج السيميائي خاصة فيما تعلق بسيمياء الفعل، للكشف عن البرامج الدرامية في النص المسرحي ومساراتها المتقاطبة التي تظهر في المستوى السطحي على شكل صراع بين الذوات الفاعلة، وبذلك سنحدد أنواع الذوات حسب ما يسنده الكاتب إليها من أدوار، سواء تعلق الأمر بطريقة رؤيتها للأفعال الدرامية أو بما تقوم به من أفعال تؤثر على المسار الدرامي.
The drama program in the theatrical text is based on a set of dramatic transformations according to a specific timeframe and place where the author tries to embody that program through an imaginary space accompanied by a parallel text explaining the situations in which the dramatic actions take place. Also in that program, the author describes the situations of the active selves based on moving the dramatic act and transforming it from one path to another in a process called, in the semiotic term, “dramatic Transformations.” On this basis, the dramatic self is the focus of the theatrical text, and the dramatic act is originally based on the presence of the dramatic self, by defining its relationship to the subject of value embodied in the theatrical text, whether the active self is relevant or separate from it. The active self becomes dominant in the dramatic path in the play, whether negative or positive. Accordingly, our study in this work was directed at following up the selves of the dramatic action (act) in the play '"El-warda wa Essiaf' (The Rose and the Swordsman) by Azzeddine Mihoubi. We follow the semiotic approach, especially in relation to the semiotics of the act, to reveal the drama programs in the theatrical text and its various paths that appear at the superficial level in the form of conflicts represented in the active selves. In doing so, we will determine the types of selves, depending on the roles assigned to them by the author, whether it is related to the way in which these selves see the dramatic acts, or through the actions they (the selves) do, which influence the dramatic trajectory.
Keywords: السيميائية الحديثة -- النصوص المسرحية -- الخطاب الروائي -- ميهوبي، عز الدين